Nano Ag sintering on Cu substrate assisted by self-assembled monolayers for high-temperature electronics packaging. (November 2021) - Liu, Canyu; Liu, Allan; Su, Yutai; Zhou, Zhaoxia; Liu, Changqing
Abstract: Sintering of nano Ag paste on bare Cu has attracted more interests recently for high-temperature electronics packaging, which offers the advantages of high reliability, cost-effective and direct bonding process. However, the current bonding methods normally need a protective atmosphere or metallization on Cu substrate to avoid oxidation. In this study, self-assembled monolayers (SAMs) were deposited on Cu substrate to suppress oxidation prior to nano Ag sintering. Thermal-compression bonding process of Cu/nano Ag/Cu joints was conducted and analysed with and without SAMs treatment. The cross-sectional characterization and shear tests were conducted to evaluate the influence of SAMs treatment. When SAMs applied, shear strength of 12.72 MPa has been achieved in the ambient atmosphere, which is much higher than the value without SAMs treatment (3.77 MPa). It has been identified that the shear mode changed from the interfaces of sintered nano Ag/Cu to inside of sintered nano Ag due to the applied SAMs. This technological approach provides a tangible and cost-effective method for high-temperature electronics packaging. Highlights: SAMs has been applied to assist the sintering process between nano Ag and bare Cu. SAMs prevent Cu surface from oxidation for improved bond formation. Bonding process has been simplified through the removal of metallization.